Enhancing the Formation and Stability of Oil-In-Water Emulsions Prepared by Microchannels Using Mixed Protein Emulsifiers - Jiao, Yan; Zhao, Yuntai; Chang, Ying; Ma, Zhaoxiang; Kobayashi, Isao; Nakajima, Mitsutoshi; Neves, Marcos A. (Frontiers in Nutrition, 2022)
Although natural emulsifiers often have many drawbacks when used alone, their emulsifying ability and stability can usually be improved unexpectedly when used in combination. In this study, monodisperse emulsions stabilized by combining two natural protein emulsifiers, i.e., whey protein isolate (WPI) and sodium caseinate (SC), in different proportions were prepared using microchannel (MC) emulsification. The influences of temperature, pH, ionic strength, and storage time on the microstructure and stability of the emulsions were examined. Analysis of the microstructure and droplet size distribution revealed that the WPI-, SC-, and mixed protein-stabilized emulsions exhibited uniform droplet distribution. The droplet size and ξ-potential of the microchannel emulsions stabilized by mixed protein emulsifiers were higher than those of the emulsions stabilized by WPI or SC separately. The emulsions stabilized by the two types of proteins and mixed emulsifiers had better stability under high salt concentrations than the synthetic emulsifier Tween 20. WPI-SC-stabilized emulsions were more resistant to high temperatures (70-90 °C) and exhibited excellent stabilization than those stabilized by WPI and SC, which was attributed to the more sufficient coverage provided by the two types of protein emulsifier layers and better protein adsorption at the oil-water interface. These results indicate that WPI-SC is a potential stabilizer for microchannel emulsion requirements. This study provides a basis for the formulation of monodisperse and stable natural emulsion systems.